2022
DOI: 10.3389/fmed.2022.851536
|View full text |Cite
|
Sign up to set email alerts
|

Vitrectomy and All-Cause and Cause-Specific Mortality in Elderly Patients With Vitreoretinal Diseases: A Nationwide Cohort Study

Abstract: PurposeTo determine the all-cause and cause-specific mortality in elderly patients with vitreoretinal diseases based on vitrectomy status.MethodsElderly patients (aged ≥ 60 years) diagnosed with vitreoretinal diseases between 2003 and 2012 using the Korean National Health Insurance Service-Senior cohort (2002–2015) were included in this nationwide population-based retrospective cohort study. The exposure of interest was vitrectomy, and information on mortality from patient inclusion until December 2015 was obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…(39) Similarly, Kim et al did not detect a correlation between vitreoretinal disease and cancer mortality in the older adults. (50) Given the convenience of obtaining the diagnosis and grading of retinopathy by fundus examination in a non-invasive manner, the findings of our study have several practical implications. Firstly, our current study found that the diagnosis of retinopathy was an independent risk factor for all-cause mortality in people over 40 years, suggesting that the general older adults population may benefit from a routine fundus examination program.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…(39) Similarly, Kim et al did not detect a correlation between vitreoretinal disease and cancer mortality in the older adults. (50) Given the convenience of obtaining the diagnosis and grading of retinopathy by fundus examination in a non-invasive manner, the findings of our study have several practical implications. Firstly, our current study found that the diagnosis of retinopathy was an independent risk factor for all-cause mortality in people over 40 years, suggesting that the general older adults population may benefit from a routine fundus examination program.…”
Section: Discussionmentioning
confidence: 93%
“…( 39 ) Similarly, Kim et al did not detect a correlation between vitreoretinal disease and cancer mortality in the older adults. ( 50 )…”
Section: Discussionmentioning
confidence: 99%